Balanced Scorecard (BSC) Dalam Pengukuran Kinerja Organisasi Sektor Publik Pada Kantor Desa di Blitar - Ni’maturohmah Ni’maturohmah; Retno Murnisari; Sura Klaudia (RISK : Jurnal Riset Bisnis dan Ekonomi, 2022)
The purpose of this study is to analyze the application of the Balanced Scorecard (BSC) method in measuring the performance of public sector organizations at the Jimbe Village Office, Kademangan District. research place at jimbe village office, Kademangan district, descriptive type of research with quantitative approach, data collection methods in the form of interviews, questionnaires and documentation using samples of people who carry out services at the jimbe village office for one month, all Jimbe Village Tools and APBDes data for the 2019-2021 fiscal year. The results of the study are that the financial perspective of the Jimbe Village Government is quite good with the economic ratio classified as economical and the effectiveness ratio is classified as effective, the financial independence ratio is relatively low and the efficiency ratio is classified as inefficient. The customer perspective of the community satisfaction index is classified as satisfied. Jimbe Village's internal business process perspective has innovated in technology-based operational activities, adequate facilities and infrastructure. The learning perspective and the growth of the device satisfaction index are classified as satisfied with various training programs.